DAMPAK KEBIJAKAN E-MONEY DI INDONESIA SEBAGAIALAT SISTEM PEMBAYARAN BARU - SOFYAN ABIDIN, MUHAMMAD (Jurnal Akuntansi AKUNESA, 2015)
This research study focuses on a payment system policy by Bank of Indonesia that aims to provide information and an overview of e-money and the impact that appears on the policy.This study also analyzes the impacts which arise when the policy is issued and menjelaskaan from a different point of view, namely from the point of view of society as a user of the e-money products. E-money it self is the output of economic policy in the payment system which aims to minimize the amount of money in circulation so that the rate of inflation can be controlled by Bank Indonesia. Payment systems using e-money is a process of modernization of the payment system that is safe, convenient, and easy which has been developed in several countries in the world. Keyword : e-money, economic policy, payment sytstem